Comparative analysis of venture capitalists investment criteria: a case from China and Pakistan / Shakeel Muhammad ... [et al.] - Muhammad, Shakeel; Li, Yaokuang; Wu, Juan; Ali, Gohar (Accounting Research Institute and UiTM Press, Universiti Teknologi MARA, 2017)
This paper evaluates a method, intended by formal investors (venture capitalists) while making sound investment decisions and selecting those successful entrepreneurs in the emerging economies by identifying their basic investment criteria. The purpose is extended to compare the criteria used by venture capitalists of both countries along with the related risk profile faced by them. The online questionnaires were sent to the venture capitalists of both countries (selected from the official entities) which are followed up by the interview (face to face and electronic). It is found that venture capitalists of both countries act almost same while evaluating the individual criteria (entrepreneur’s personality and experience) and corporate criteria (Product and Market characteristics). In terms of institutional or environmental criteria, Pakistani VCs are more demanding then Chinese VCs due to the lack of support from the financial and legal institutions. Further, Pakistani VCs attracted by the environmental level risk like country and geographical risk whereas Chinese VCs concentrates on the socio-culture and trade risk. While the VCs of both countries react in the same way to the venture and team level risk. Investment is a multi-stage process. The researchers are encouraged to enhance the investment criteria along with the stages of investment (deal-origination, deal-structuring and due-diligence).